The Private Film Collection of Eva Braun
Germany, 1936--1943. Home footage of life at Hitler's mountain refuge--the Berghof. Spectacular Alpine panoramas highlight scenes of Nazi leaders, foreign diplomats and local visitors, and Eva Braun herself. Views of Hitler in war and peacetime, chatting with children, conferring with subordinates, relaxing after victories and recovering after Stalingrad. A unique picture of the Führer's private life.